Differential SLC6A4 methylation: a predictive epigenetic marker of adiposity from birth to adulthood - Lillycrop, K.; Garratt, E.; Titcombe, P.; Melton, Phillip; Murray, R.; Barton, S.; Clarke-Harris, R.; Costello, P.; Holbrook, J.; Hopkins, J.; Childs, C.; Paras-Chavez, C.; et al. (Nature Publishing Group, 2019)
Background: The early life environment may influence susceptibility to obesity and metabolic disease in later life through epigenetic processes. SLC6A4 is an important mediator of serotonin bioavailability, and has a key role in energy balance. We tested the hypothesis that methylation of the SLC6A4 gene predicts adiposity across the life course. Methods: DNA methylation at 5 CpGs within the SLC6A4 gene identified from a previous methyl binding domain array was measured by pyrosequencing. We measured DNA methylation in umbilical cord (UC) from children in the Southampton Women’s Survey cohort (n = 680), in peripheral blood from adolescents in the Western Australian Pregnancy Cohort Study (n = 812), and in adipose tissue from lean and obese adults from the UK BIOCLAIMS cohort (n = 81). Real-time PCR was performed to assess whether there were corresponding alterations in gene expression in the adipose tissue. Results: Lower UC methylation of CpG5 was associated with higher total fat mass at 4 years (p = 0.031), total fat mass at 6–7 years (p = 0.0001) and % fat mass at 6–7 years (p = 0.004). Lower UC methylation of CpG5 was also associated with higher triceps skinfold thickness at birth (p = 0.013), 6 months (p = 0.038), 12 months (p = 0.062), 2 years (p = 0.0003), 3 years (p = 0.00004) and 6–7 years (p = 0.013). Higher maternal pregnancy weight gain (p = 0.046) and lower parity (p = 0.029) were both associated with lower SLC6A4 CpG5 methylation. In adolescents, lower methylation of CpG5 in peripheral blood was associated with greater concurrent measures of adiposity including BMI (p = 0.001), waist circumference (p = 0.011), subcutaneous fat (p = 0.001) and subscapular, abdominal and suprailiac skinfold thicknesses (p = 0.002, p = 0.008, p = 0.004, respectively). In adipose tissue, methylation of both SLC6A4 CpG5 (p = 0.019) and expression of SLC6A4 (p = 0.008) was lower in obese compared with lean adults. Conclusions: These data suggest that altered methylation of CpG loci within SLC6A4 may provide a robust marker of adiposity across the life course.